Mulligan mobilization versus traction in lumbar facet joint syndrome: randomized controlled trial - Elgendy, Mohammed Hussien; Habib, Ahmed Abduallah; Ibrahim, Ramy Edward; Lasheen, Yasser Ramzy (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The aim of this study was to investigate and compare the effect of Mulligan mobilization, lumbar traction and their combination on pain, functional disability and facet tropism in patients with facet joint syndrome. Sixty patients with facet joint syndrome from both sexes and aged 30 to 50 years participated in the randomized controlled trial design. They were referred from orthopedic and neurological clinics and divided into four groups as follows: group A received Mulligan mobilization and conventional treatment, group B received lumbar traction and conventional treatment, group C received Mulligan mobilization in combination with lumbar traction in addition to conventional treatment, while group D (control group) received the conventional treatment only. All participants received 3 treatment sessions per week for one month. The assessments were done before and after one month of treatment using Visual Analogue Scale (VAS) for pain, Oswestry Disability Index (ODI) for functional disability, and magnetic resonance image (MRI) for facet joint tropism. Statistically significant improvement was found in pain and functional disability in all four groups post-treatment (p<0.05), compared to pre-treatment, with the study groups (A, B and C) having a higher improvement than the control group (D). The improvement in group C was significantly higher than in groups A and B (p<0.05), and the improvement in group A was significantly higher than in group B (p<0.05). Regarding the facet joint tropism, there was a statistically significant improvement in the four groups post-treatment (p<0.05) compared with pre-treatment, with higher significant improvements in the study groups (A, B, C) in comparison with the control group (D). There was no statistically significant difference in tropism between groups A, B and C. The combination of Mulligan mobilization and lumbar traction (group C) was the most effective treatment for relieving pain and functional disability in patients with facet joint syndrome. Regarding facet tropism, there was a statistically significant improvement with all the treatments, but the conventional treatment produced the lowest improvement.